Long-Term Retrospective Analysis of Microvascular Decompression in Patients With Recurrent Trigeminal Neuralgia - Liu, Jiayu (Front Neurol, 2020)
Objective: To explore the clinical characteristics of patients with recurrent trigeminal neuralgia (TN) and the experience of microvascular decompression (MVD) in the treatment of such patients. Methods: We retrospectively analyzed clinical data, imaging examination results, surgical methods, and treatment efficacies in 127 patients with recurrent typical TN from January 2005 to December 2014. Results: The age of the recurrent group was higher than that of the non-recurrent group (p < 0.05). The duration of pain before the first MVD procedure was longer in the recurrent group than in the non-recurrent group (p < 0.05). Patients in the recurrent group were more likely to have compression of the trigeminal nerve by the vertebrobasilar artery (VBA) or multiple vessels than patients in the non-recurrent group (p < 0.05). A Kaplan–Meier curve showed a median pain-free survival of 12 months after the first MVD procedure. The severity of pain (preoperative visual analog scale [VAS] score) in patients with recurrence was lower than that in patients with first-onset TN (p < 0.05). Vessel compression, Teflon compression or granuloma and arachnoid adhesion were considered the main causes of recurrence. Postoperative Barrow Neurological Institute (BNI) scores in the redo MVD group were excellent (T = 2) for 69 patients (53.33%) and good (T = 3) for 46 patients (36.22%). The postoperative follow-up was 63–167 months (105.92 ± 25.66). During the follow-up, no recurrence was noted. All complications were cured or improved. Conclusions: Microvascular decompression (MVD) is an effective surgical method for the treatment of TN. For recurrent patients, reoperation can achieve good results.